Analisis Tingkat Kerawana Banjir Daerah Distrik Masni Kabupaten Manokwari Provinsi Papua Barat - Erikha Maurizka Mayzarah; Shopia Widya Selly Rumayomi; Rana Wiratama (Mataram University, 2026)
This study aims to analyze flood susceptibility in Masni District, Manokwari Regency, West Papua Province, using a geospatial approach based on Geographic Information Systems (GIS). The study area is characterized by complex geological and geomorphological conditions and has experienced significant flood events, notably in 2020 and 2024, which affected thousands of residents and infrastructure. The research employed overlay and scoring methods by integrating six main parameters: lithology, rainfall, slope, elevation, land use, and distance from rivers. Each parameter was assigned a weight and score according to its relative influence on flood occurrence. The data utilized in this study were derived from secondary sources, including DEMNAS, RBI maps, CHIRPS rainfall data, land use imagery, and field observations. The analysis results indicate that areas composed of alluvial deposits, gentle slopes, high rainfall intensity, low elevation, residential land cover, and proximity to rivers exhibit high flood susceptibility. The resulting flood susceptibility map classifies the study area into several zones: very high, high, moderate, and low susceptibility. This research is expected to serve as a reference for spatial planning and flood disaster mitigation strategies, as well as to provide valuable information for local communities and regional authorities.